PEMERIKSAAN FORMALIN PADA TAHU YANG BEREDAR DI PASAR BATUSANGKAR MENGGUNAKAN KALIUM PERMANGANAT (KMnO4) DAN KULIT BUAH NAGA - KHAIRA, KUNTUM (IAIN Batusangkar, 2015)
Formalin is a toxic chemical that is commonly used as a preservative for biological samples and in various industries. But in practice many abused formaldehyde as a preservative foods such as tofu, meatballs, anchovies, etc. wet fish. When food is consumed can cause interference with the metabolism of the body's organs and systems. A research on the investigation of formaldehyde, especially in out circulating in the market Batusanggkar. Examination carried out by using potassium permanganate (KMnO4) and dragon fruit skin by observing the color changes. Examination of formalin in 5 samples showed similar results to know that the 5 samples contain formaldehyde are all positive.Key word: formalin, tahu, KMNO4, Dragon Fruit skin